Existence of observable sets for control Systems on Lie groups - Akyar, B. (2025)
In this paper, we introduce the concept of observable sets for control systems. For this reason, we review general control systems on Lie groups with observation (output) functions and give the solution of the affine control system on a connected Lie group. Then, we study the existence of observable sets for linear control systems on examples.